Short, enantioselective, gram-scale synthesis of (−)-zephyranthine. Issue 27 (21st June 2021) - Zhao, Yuxiang; Zhu, Yanren; Ma, Guolan; Wei, Qi; Yang, Shaoxiong; Zeng, Xiaoyu; Zhang, Hongbin; Chen, Jingbo
Abstract : A reasonable synthesis design by strategically integrating functional group manipulation into the ring system construction resulted in a short, enantioselective, gram-scale total synthesis of (−)-zephyranthine. Abstract : A reasonable synthesis design by strategically integrating functional group manipulation into the ring system construction resulted in a short, enantioselective, gram-scale total synthesis of (−)-zephyranthine. The concise route includes a catalytic Michael/Michael cascade for the asymmetric synthesis of a penta-substituted cyclohexane with three contiguous stereogenic centers, a remarkable 8-step one-pot operation to easily assemble the zephyranthine tetracyclic skeleton, the regioselective construction of a double bond in the C ring and an asymmetric dihydroxylation. This synthesis is also flexible and paves a potential path to a variety of cyclohexylamine-fused tricyclic or polycyclic alkaloids.